Consumption of ultra-processed foods does not affect neuromuscular and cardiovascular fitness but alters gut microbiota in elite basketball players - Ilić, Ana; Žučko, Jurica; Starčević, Antonio; Novak, Dario; Rumbak, Ivana; Hadžić, Edin (Croatian journal of food science and technology, 2024)
To enhance recovery, athletes often consume ready-to-eat foods, specialized sports foods and/or supplements that belong to the group of ultra-processed foods (UPFs), which may affect their health. The aim of this study was to estimate consumption of UPFs in basketball players and to determine whether there is a difference in anthropometric characteristics, neuromuscular and cardiovascular fitness and microbiota composition between players in relation to the proportion of daily energy from processed foods. The study involved 17 elite male basketball players (>18 years) from Croatia during the competitive season. After cluster analysis of daily energy contribution from NOVA food groups, 35% of players were clustered into higher UPFs consumption group. No differences in anthropometric characteristics, neuromuscular and cardiovascular fitness were observed between players who consumed more UPFs and those who consumed less UPFs. Players with higher consumption of UPFs had lower abundance of the order Veillonellales-Selenomonadales in their respective microbiotas, more precisely, of family Veillonellaceae (p = 0.040) and the genus Agathobacter (p = 0.025). These results suggest that the consumption of UPFs did not affect athletes’ performance but does impact their gut microbiota. Further studies on this issue are warranted to establish nutritional guidelines for athletes regarding the consumption of UPFs.